Optimalisasi pelayanan administrasi perbankan syariah melalui evaluasi kepuasan nasabah di BSI Gresik - Novi Darmayanti; Erika Sapitri Handayani; Mawar Umu Salamah; Nur Fidya Putri (Nur Science Institute, 2026)
This community service activity aims to analyze the level of customer satisfaction with administrative services at Bank Syariah Indonesia (BSI) Gresik Branch as a basis for formulating a strategy for continuous service quality improvement. The method used was a quantitative descriptive survey with a questionnaire instrument based on the five dimensions of SERVQUAL, including tangibility, reliability, responsiveness, assurance, and empathy, which were distributed to active BSI customers through a purposive sampling technique. The implementation of the activity included three main stages: preparation, implementation, and evaluation. The analysis results showed an average satisfaction index of 3.99 on a scale of 5, with the assurance dimension obtaining the highest score of 4.32 and the responsiveness dimension obtaining the lowest score of 3.67. These findings indicate that although customer trust in employee competence has been well established, aspects of response speed and service personalization still require more intensive attention and improvement. This activity recommends optimizing the queuing system, training employee soft skills, and implementing periodic satisfaction evaluations to realize excellent service standards that align with the values of Islamic banking.